The Present State of Unpopular Music - Beckwith, John (Intersections)

(untitled) (Canadian University Music Society / Société de musique des universités canadiennes, 2007)
When asked, "what kind of music do you write?" the late composer Harry Somers always replied "unpopular music." Whatever it is called, the category has undergone marked changes recently. SOCAN's 1992 transference of control from its "classical" wing to its commercial sector was, for the Canadian musical scene, a historic indicator of change.The death of modernism has become a critical cliché. Recent studies declare the end of "classical" music cultivation in the U.S.A. Composers are enjoined to conform to the vocabulary of U.S. pop. A simplified and meditative popular approach is espoused by some, notably (in Canada) Christos Hatzis.Despite signs of decline, a minority consumership for new "unpopular" works of diverse kinds remains strong. For a marginalized Canadian, local communication is genuine, and small is beautiful.